ANALISIS STRATEGI PERKEMBANGAN TENUN MELAYU SIAK DI KABUPATEN SIAK - Arista Elda Marisa; Azwar Harahap; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine what factors are the strengths, weaknesses, opportunities and threats of Siak Malay Woven Fabric in Siak Regency. This research was conducted in Siak Regency of Riau Province. Siak Regency was chosen as the research location because Siak is one of the weaving industry location in Riau Province. The population in this research is Siak Woven Fabric according to Department of Industry and Trade Cooperatives in Siak Regency There are 4 units of Siak Malay Woven Fabric business active in Siak Regency. Method of data analysis using SWOT analysis. The result of the research shows that SWOT quadrant diagram is known that Siak Malay Tenun Industry is in quadrant I position, where in this position a business or industry has a strong position and a chance to develop. In this position the strength is greater than the weakness and greater opportunities of the threat so that the appropriate strategy to be applied to Siak Woven Fabric Industry is the S-O Strategy. This is a very favorable situation. The industry has opportunities and strengths so that it can take advantage of the existing opportunities strategies that must be implemented in these conditions is to support an aggressive growth policy. Strategies that can be done is to increase production, maintain the quality of weaving produced, market development and innovate weaving and increase promotion.Keywords : SWOT, Malay, Woven-Fabric, Industry, Strategy, Marketing